1974
DOI: 10.4039/ent106897-9
|View full text |Cite
|
Sign up to set email alerts
|

Phytophagous Arthropod Fauna of Crownvetch in Pennsylvania

Abstract: Can. Ent. 106: 897-908 (1974) A survey of the phytophagous arthropod fauna of the introduced legume crownvetch, Coronilla varia L., was conducted in Pennsylvania during 1971-73. Samples were taken from large forage fields, highway plantings used for erosion control, and greenhouses. Emphasis was placed on determining what known pests of other forage legumes are associated with crownvetch and on clarifying the relationship of the species to the host plant. Species were categorized as primary, secondary, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Due to its attractiveness as groundcover and forage (Reynolds et at, 1969;Bums et at, 1969Bums et at, , 1972, and its ability to escape cultivation, e. varia is becoming increasingly abundant throughout much ofthe eastern and midwestern United States. By 1974, nearly 30,000 acres of'C varia had been planted along highway slopes in Pennsylvania alone (Wheeler, 1974). Moreover, with continued naturalization, sympatry between e. varia and e. philodice is likely to increase since the typical habitats of e. varia, M. sativa, T. pratense, and M. alba (roadsides, waste places, and other disturbed areas) are very similar (Fernald, 1950).…”
Section: Study Organismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its attractiveness as groundcover and forage (Reynolds et at, 1969;Bums et at, 1969Bums et at, , 1972, and its ability to escape cultivation, e. varia is becoming increasingly abundant throughout much ofthe eastern and midwestern United States. By 1974, nearly 30,000 acres of'C varia had been planted along highway slopes in Pennsylvania alone (Wheeler, 1974). Moreover, with continued naturalization, sympatry between e. varia and e. philodice is likely to increase since the typical habitats of e. varia, M. sativa, T. pratense, and M. alba (roadsides, waste places, and other disturbed areas) are very similar (Fernald, 1950).…”
Section: Study Organismsmentioning
confidence: 99%
“…Second, colonization of C. varia appears to be particularly facile for species, such as C. philodice, that presently feed on M. sativa. Nearly 50% of herbivorous insect species that have colonized C. varia in Pennsylvania are primary herbivores of alfalfa (Pimentel and Wheeler, 1973;Wheeler, 1974). Third, C. eurytheme, which has a host plant range nearly identical to that ofC.…”
Section: Oviposition On C Varia In Naturementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its aggressive vegetative growth, crown vetch plants produce copious amounts of pinkish-white to deep pink flowers in long-stalked clusters. Though crown vetch has been recognized as a management problem for habitats such as prairies and savannas (Solecki 1997), limited research has been published on its impacts at the species, community, and ecosystem levels (e.g., Wheeler 1974;Walck et al 1999;Symstad 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, plastic film does not increase the abundance of soil nutrients and has negative environmental impacts, and both plastic film and straw mulch impose transportation expenses and other costs each year. As a perennial legume, crown vetch can live for several years if well managed and sprout in late March each year after being sown in the first year, and it can form root nodules, control weeds, prevent soil erosion, and improve soil fertility (Wheeler, 1974;Symstad, 2004). As a legume, crown vetch can mitigate nitrogen competition due to its ability to fix atmospheric N 2 via root nodules, compared to other nonlegume species, and other similar studies found that nitrogen competition was mitigated by legume grass cover systems (King & Berry, 2005;Messiga et al, 2015).…”
mentioning
confidence: 99%